Noma (Cancrum Oris): report of a Mexican case - Figueroa-Hernández , María Fernanda; Macedo-Pérez, Marysol; Mosqueda-Taylor , Adalberto; Ramírez-Hinojosa , Juan Pablo; Berumen-Glinz , Cristina; Santamaria-Linares , Eric; Vega-Memije , Maria Elisa; Toussaint-Caire , Sonia (Journal of Oral Diagnosis, 2025)
“Cancrum oris” (noma) is a severe necrotizing infectious disease that typically begins as a localized ulcerative lesion of the oral mucosa and rapidly progresses to cause extensive destruction of the orofacial tissues. It predominantly affects individuals with compromised immunity and is strongly associated with malnutrition, poor oral hygiene, and systemic conditions such as HIV infection. We presented the case of a 44-year-old Mexican woman, living with untreated HIV infection, who presented with clinical features consistent with noma in Mexico City. Her management required a coordinated multidisciplinary approach. Although noma is a rare condition in the Americas, it remains a significant public health concern in sub-Saharan Africa. Identified risk factors include extreme poverty, severe malnutrition, inadequate sanitation, and underlying immunosuppressive states such as HIV/AIDS. Histopathological findings demonstrated sharply demarcated necrosis of the surface epithelium, accompanied by peripheral acanthosis and cytoplasmic ballooning of marginal epithelial cells. The underlying dermis showed marked edema with separation of collagen bundles, a dense polymorphonuclear neutrophilic infiltrate, and dilated blood vessels filled with inflammatory cells. Numerous phagocytosed microorganisms were identified, including Gram-negative cocco-bacilli and cocci of variable morphology. Is a polymicrobial infection, the most common pathogen identified is Fusobacterium necrophorum, the synergistic action of multiple anaerobic and facultative organisms, along with their virulence factors, contributes to the fulminant tissue destruction characteristic of the disease. Treatment involves aggressive surgical debridement, antibiotic therapy, and addressing nutritional deficiencies. Noma is a preventable but neglected disease that primarily affects impoverished populations. This case represents both a diagnostic and therapeutic challenge, and to our knowledge, constitutes the first documented instance of adult-onset noma in Mexico. A previous report from 1991 described a pediatric case, but no cases involving adults have been published in the Mexican medical literature to date.